Salas multisseriadas: compreensões sobre a organização da prática docente - Oliveira, Francisca Rayane Gomes de (Universidade Federal Rural do Semi-Árido, 2019)
The present work consists of a monographic study carried out with three teachers who teach in multi-series classes, in two schools with multi-series teaching organization. From a qualitative research with visits to schools, semi-structured interview and notes in field diary through the following question: How do teachers who teach in multi-series rooms organize their work in the process of teaching learning? And the general objective was: To know the work methodologies used by teachers working in multi-series classrooms. As specific objectives, the aim was to identify ways of time management by teachers in multiseries rooms, to understand how teachers work the content in the context of multi-series rooms and to analyze the forms of organization of the class group, promoted by teachers in relation to working with classes multisseries. Initially, a review is presented on the organization of multi-grade teaching, in which it was noticeable that this model of teaching organization arises at the moment that the need for an education for all is addressed, with reflections on the attendance to small audiences of students in distant or hard to reach places. In continuity, we began to reflect on the particularities related to the multi-series rooms. We approach from the training of teachers, pedagogical support, to the attention of the government to this reality of teaching. Our research has shown that teachers indicate that they can develop satisfactory work despite the gaps / limits of activity in multisite rooms. In addition, this study pointed out that multi-session rooms can provide good results in teachinglearning relationships, although in the present configuration it needs a great effort/commitment on the part of the teachers in disregard of the conditions placed on them.
Monografia
Keywords: Salas multisseriadas; Ensino; Escolas do campo; Prática docente; Multi-Serial rooms; Teaching; Country schools; Teaching practice; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL